2019
DOI: 10.1097/md.0000000000016772
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates the increase of ultrasonographic optic nerve sheath diameter as a surrogate for intracranial pressure in patients undergoing robot-assisted laparoscopic prostatectomy

Abstract: Background:Pneumoperitoneum and steep Trendelenburg position during robot-assisted laparoscopic prostatectomy (RALP) can increase intracranial pressure (ICP). Dexmedetomidine, a highly selective alpha-2 adrenergic receptor agonist, can cause cerebral vasoconstriction and decrease cerebral blood flow by stimulating the postsynaptic alpha-2 adrenergic receptors on cerebral blood vessels. However, the effects of dexmedetomidine on ICP are controversial and have not been evaluated during RALP under the establishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…HR and MAP of patients in surgical intensive care unit after major abdominal surgery were significantly lower in the dexmedetomidine group than in the propofol group [32] . During robot-assisted laparoscopic prostatectomy, the HR of dexmedetomidine group was significantly lower than that of saline group Chin Med Sci J ISSN 1001-9294 CN 11-2752/R DOI: 10.24920/004088 [33] . Among conscious patients undergoing carotid endarterectomy, the intraoperative HR, SBP, and DBP in dexmedetomidine group were lower than those in metoprolol and labetolol groups [34] .…”
Section: Discussionmentioning
confidence: 92%
“…HR and MAP of patients in surgical intensive care unit after major abdominal surgery were significantly lower in the dexmedetomidine group than in the propofol group [32] . During robot-assisted laparoscopic prostatectomy, the HR of dexmedetomidine group was significantly lower than that of saline group Chin Med Sci J ISSN 1001-9294 CN 11-2752/R DOI: 10.24920/004088 [33] . Among conscious patients undergoing carotid endarterectomy, the intraoperative HR, SBP, and DBP in dexmedetomidine group were lower than those in metoprolol and labetolol groups [34] .…”
Section: Discussionmentioning
confidence: 92%
“…Surgical procedures in this specific condition might have consequences including neurologic deterioration in patients with cerebrovascular disease (Casati et al, 2007; Gainsburg, 2012). Previous studies reported that pneumoperitoneum and the ST position caused a significant reduction in cerebral oxygen saturation in elderly patients (Casati et al, 2007) as well as increased ICP during robotic prostatectomy (Jun et al, 2018; Yu et al, 2018, 2019). These unfavourable changes were associated with cerebral ischaemia, postoperative cognitive dysfunction, postoperative delirium, and longer hospital stay (Casati et al, 2005; Green, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…A typical optic nerve sheath is less than 5 mm and is considered to be a good neurological outcome for post-CA patients. Future studies should establish the best cutoff values for ONSD that correlate with poor neurological outcome and that can be standardized for diverse subgroups categorized by age, temperature treatment, and condition [ 24 ].…”
Section: Discussionmentioning
confidence: 99%